1981
DOI: 10.1073/pnas.78.2.1162
|View full text |Cite
|
Sign up to set email alerts
|

Complete amino acid sequence of bovine thymosin beta 4: a thymic hormone that induces terminal deoxynucleotidyl transferase activity in thymocyte populations.

Abstract: The amino acid sequence of thymosinj,84, a polypeptide isolated from calf thymus, was determined. Thymosin 184 is composed of 43 amino acid residues and has a molecular weight of 4982 and an isoelectric point of 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
145
0
8

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(154 citation statements)
references
References 33 publications
1
145
0
8
Order By: Relevance
“…First identified from a cytokine-like activity, Tβs play significant roles in various physiological processes. (Low et al, 1981). Later studies showed that Tβs' mRNA and protein levels were changed rapidly during differentiation or by different stimuli (Hall, 1991;Huff et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First identified from a cytokine-like activity, Tβs play significant roles in various physiological processes. (Low et al, 1981). Later studies showed that Tβs' mRNA and protein levels were changed rapidly during differentiation or by different stimuli (Hall, 1991;Huff et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In 1990, Safer et al [l] identified a peptide of approximately 5 kDa in platelets that preferentially binds to G-actin, even in the presence of high salt, thus stabilizing the monomeric pool of G-actin. This protein was found to be identical to thymosin p4 (Tp4) [2], a peptide originally believed to be a thymic hormone [3] and able to modulate the immune responsiveness of peripheral lymphocytes [4, pected presence of Tp4 and related peptides at high concentrations in almost any eukaryotic cell shed doubts on this function [l, [6][7][8][9][10].…”
mentioning
confidence: 99%
“…Thymosin-β4 was first isolated from calf thymosin fraction 5; it is also found in various organs such as the spleen, thymus, liver that exhibit biological activity on the immune system cells. Thymosin-β4 has been reported to suppress the mixed lymphocyte proliferative response, 14 induce the expression of terminal deoxynucleotidyl transferase in T cells, 15 inhibit the migration of macrophages in vitro, 16 and inhibit cytokine production by neutrophils after tumor necrosis factor (TNF)-α stimulation. 17 TGF-β, which can be released by thymocyte and thymic epithelial cells, almost inhibits all lymphocyte proliferation, including mitogen-and allogenic antigen-induced T-cell proliferation and Staphylococcus aureus Cowan I (SAC)-induced and IL-2 independent B-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%